2017
DOI: 10.3389/fendo.2017.00074
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Salivary Cytokines for Diagnosis of both Trauma-Induced and Genetic Heterotopic Ossification

Abstract: PurposeHeterotopic ossification (HO) occurs in the setting of persistent systemic inflammation. The identification of reliable biomarkers can serve as an early diagnostic tool for HO, especially given the current lack of effective treatment strategies. Although serum biomarkers have great utility, they can be inappropriate or ineffective in traumatic acute injuries and in patients with fibrodysplasia ossificans progressiva (FOP). Therefore, the goal of this study is to profile the cytokines associated with HO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…Concentrations of IL-1β remained unchanged, while IL-6 and TNFα were undetectable; this may reflect the nature of the intervention, as impact on these pro-inflammatory cytokines varies greatly with exercise duration and intensity [13]. Recent studies indicate that levels of salivary cytokines can be correlated to those found in serum in some disease models [35]. It is worth emphasizing again that our sample was young, active and healthy, thus, results may be of even greater magnitude among those at risk or with existing chronic conditions associated with low-grade systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of IL-1β remained unchanged, while IL-6 and TNFα were undetectable; this may reflect the nature of the intervention, as impact on these pro-inflammatory cytokines varies greatly with exercise duration and intensity [13]. Recent studies indicate that levels of salivary cytokines can be correlated to those found in serum in some disease models [35]. It is worth emphasizing again that our sample was young, active and healthy, thus, results may be of even greater magnitude among those at risk or with existing chronic conditions associated with low-grade systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous lineage tracing demonstrated that many mesenchymal stem/progenitor subpopulations, including Prx-cre [28], Scleraxis-cre [29], Nfatc1-cre [30], MX1-cre [31], and Wnt1-cre [32], in addition to the three subpopulations (Tie2-cre, Gli1-creER, and Glast-creERT) we have tested in this study, contribute significantly to HO [13–15, 31]. A key question in this study was whether these subpopulations contribute to HO through the MSC niche.…”
Section: Discussionmentioning
confidence: 99%
“…Local wound site expression of these markers as assessed by qPCR was generally found to temporally overlap with rise and fall of detected levels within the serum. (178) Within the same model, increased levels of MCP‐1 were also found in murine saliva, although other assayed markers were too low for detection . Increased inflammatory markers have also been observed among human traumatic HO, both at the local and systemic level.…”
Section: Basic Biologic Features Of Heterotopic Ossificationmentioning
confidence: 94%
“…Correlation of levels of inflammatory cytokines to bone formation is best documented in nongenetic HO. For example, in a mouse model combining cutaneous burn with Achilles tenotomy, increased serum levels of TNFα, IL‐1β, IL‐6, and MCP‐1 were associated with HO formation . Local wound site expression of these markers as assessed by qPCR was generally found to temporally overlap with rise and fall of detected levels within the serum.…”
Section: Basic Biologic Features Of Heterotopic Ossificationmentioning
confidence: 99%